The Analysis Of Blood Supply Chain Performance Based On Supply Chain Operation Reference Model And Causal Loop Diagram Approach - Mulyadi, Agus; Meirizha, St. Nova; Qurthuby, Muhammad; Sundari, Mela (Politeknik APP Jakarta, 2023)
This study evaluates the effectiveness of the blood supply chain and determines potential causes of substandard supply chain performance. Unfulfilled demand for blood at UDD PMI Indragiri Hilir in 2021 reached 970 bags, or 14.1% of all orders. The method used is SCOR (supply chain operation references) and CLD (cause loop diagram). The novelty of this research is applying the SCOR model to holistically measure the blood supply chain's performance and determine the leading causes of low performance. The total value of supply chain performance is 77.78, which is a good category. The results show that Five matrices fall into the low-performance process on the Production attribute (28.24), Capacity Utilization Screening (37.50), Capacity Utilization of Blood Quarantine Storage Cabinets (39.01), Capacity Utilization of Healthy Blood (44.44), and Capacity Utilization Crossmatch (33.3). Based on CLD analysis, potential root causes of the low performance of the supply chain with the CLD model are five low-performance matrices on production attributes influenced by voluntary donors and replacement donors, the number of donors, and blood tapping.